Sublobar resections—current evidence and future challenges - Cao, Christopher; Tian, David H.; Wang, Daniel R.; Chung, Caroline D.; Gossot, Dominique; Bott, Matthew (Journal of Thoracic Disease; Vol 9, No 12 (December 29, 2017): Journal of Thoracic Disease, 2017)
Several factors have contributed to a heightened interest in the oncologic efficacy of sublobar resections versus lobectomies for patients with non-small cell lung cancer (NSCLC). Firstly, the increased detection of early-stage disease in targeted screening programs has identified a growing number of patients with smaller tumours, which are more amenable to sublobar resections compared to tumours of higher clinical stage (1).